A Retrospective Study Comparing the Loss of Anchorage following the Extraction of Maxillary First or Second Premolars during Orthodontic Treatment with Fixed Appliances in Adolescent Patients. (December 2017) - Haque, Samantha; Sandler, Jonathan; Cobourne, Martyn T.; Bassett, Paul; DiBiase, Andrew T.
Introduction: This retrospective study assessed the difference in anchorage loss using 3D superimposition of study models between cases treated with extraction of maxillary first premolars and maxillary second premolars carried out in orthodontic specialist practice. Method: Sixty subjects who have undergone extractions of either maxillary first or second premolars as part of their orthodontic treatment were selected. Eligibility criteria included patients with a Class I, mild Class II or III malocclusions, mild-to-moderate crowding with no anchorage reinforcement. Pre- and post-treatment maxillary dental study cases were scanned using a surface laser scanner to produced 3D digital images which were superimposed using areas of stability on the anterior hard palate. Anchorage loss was measured by the mesial movement of the maxillary first permanent molar. Results: The mean mesial movement for the maxillary first molars, when adjusted for confounding factors was 4.7 mm (SD 1.6) in the maxillary first premolar extraction group and 4.6 mm (SD 1.6) in the maxillary second premolar extraction group. Conclusions: There is no difference in anchorage loss when comparing the extraction of the maxillary first premolars to the extraction maxillary second premolars.